EKSISTENSI DAN URGENSI TAFSIR KONTEMPORER - Utang Abdurrahman (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2015)
A contemporary quranic interpretation method on leadership consists of two aspects; first is explaining the meaning of al-Quran to society with the practical and interesting languange meaning. Second is explaining it through the various meanings that are directly related with the urgent and significant aspect in human life. This paper uses descritive-analitical method and sopported by thematic and semantic approaches. This paper concludes that contemporary quranic interpretation on leadership can be understood through interprete verse with verse, al-Quran with al-Hadith, exploring the meaning of the text in accordance with the truly meaning, and the aim of the Quranic redaction completely according to mufassirin. This way is commonly used by contemporary quranic intepretation on leadership which is namely tafsir bi al-ma’tsur and tahlily.